Relativizing effects of high intensity interval training vs continuous moderate - Bruno Nicanor Mello da Silva; Leony Morgana Galliano; Fabrício Boscolo Del Vecchio (Revista Brasileira de Cineantropometria e Desempenho Humano)
The production of systematic reviews and meta-analysis increased substantially. In this sense, we highlight those comparing Moderate-Intensity Continuous Training (MICT) and High-Intensity Interval Training (HIIT). It is known that meta-analyses of well-conducted studies are considered as a superior level of scientific evidence; therefore, it is relevant to critically analyze all those articles, especially speaking about the absence of differences between MICT and HIIT reported in previous studies. Widely, analyzing studies included in a meta-analysis frequently is possible to identify a lack of crucial information to the understanding of the exercise intervention, and this can skew readers interpretation and may conduct an equivocate comprehension of the results. In meta-analysis regarding the effects of MICT and HIIT in body composition, the relativization of the full length of training time of each intervention is frequently lacking. Data from previously published meta-analysis was reanalyzed, verifying higher relative reductions of body fat percentage to the HIIT group in comparison to the MICT group when considered the duration of interventions. In this sense, we suggest that all meta-analysis about this subject need not only to provide complete analysis in body composition but also consider analysis relativized of time spent training.